The Impact of Post-Recession State Revenue Reductions on Maine's Municipalities - Shaw, Emily (Maine Policy Review, 2013)
Maine municipalities have received substantially less revenue from the state over the past several years, due to a combination of financial pressures on state budgets and state administrative policy preferences. The result is that municipalities have been forced to restructure the provision and funding of local services through a combination of reducing spending in some categories, raising additional money from residents and other users of town services, or taking on additional municipal debt. However, on average, Maine’s municipalities have so far been unable to reduce their total spending. This discussion of municipal responses to reduced state revenue is based on analyzing responses to the 2007–2011 Maine Municipal Association fiscal surveys of municipal revenues and expenditures.
Keywords: Maine; municipal revenue; taxes